Unity Club For Integration, Public Universities' Routes To Excellence - Safei, Su'aidi (New Straits Times Press, 2004)
National Technical University College of Malaysia (KUTKM) was the first public university to form a Unity Club that sought to integrate the multiethnic, multireligious and multicultural student population. The club was formed in 2002 as a result of the vision and idea mooted by the former Prime Minister Tun Dr.Mahathir Mohamad.